Epitaxial Growth of Lattice‐Mismatched Core–Shell TiO2@MoS2 for Enhanced Lithium‐Ion Storage. Issue 20 (9th April 2016) - Dai, Rui; Zhang, Anqi; Pan, Zhichang; Al‐Enizi, Abdullah M.; Elzatahry, Ahmed A.; Hu, Linfeng; Zheng, Gengfeng
Abstract : Core–shell structured nanohybrids are currently of significant interest due to their synergetic properties and enhanced performances. However, the restriction of lattice mismatch remains a severe obstacle for heterogrowth of various core–shells with two distinct crystal structures. Herein, a controlled synthesis of lattice‐mismatched core–shell TiO2 @MoS2 nano‐onion heterostructures is successfully developed, using unilamellar Ti0.87 O2 nanosheets as the starting material and the subsequent epitaxial growth of MoS2 on TiO2 . The formation of these core–shell nano‐onions is attributed to an amorphous layer‐induced heterogrowth mechanism. The number of MoS2 layers can be well tuned from few to over ten layers, enabling layer‐dependent synergistic effects. The core–shell TiO2 @MoS2 nano‐onion heterostructures exhibit significantly enhanced energy storage performance as lithium‐ion battery anodes. The approach has also been extended to other lattice‐mismatched systems such as TiO2 @MoSe2, thus suggesting a new strategy for the growth of well‐designed lattice‐mismatched core–shell structures. Abstract : A controlled synthesis of lattice‐mismatched core–shell TiO2 @MoS2 nano‐onion heterostructures is developed, using unilamellar Ti0.87 O2 nanosheets as the starting material and the subsequent epitaxial growth of MoS2 on TiO2 . The formation of these core–shell nano‐onions is attributed to an amorphous layer‐induced heterogrowth mechanism. The core–shell TiO2 @MoS2 nano‐onion heterostructures exhibit significantly enhanced energy storage performance as lithium‐ion battery anodes.